Effective blood pressure reduction: results of the regional program “DOVERIE” - N. V. Dobryninа; S. S. Yakushin (Российский кардиологический журнал)
In clinical practice, quite often the practitioner faces difficulties in correcting arterial pressure in patients with arterial hypertension. Patients mostly for various reasons prefer to be treated with generic drugs, sometimes to the detriment of the effectiveness of treatment. The regional study conducted by us clearly showed the presence of additional possibilities of the original drug Prestans (Servier, France) in reducing blood pressure compared to equivalent dosages of generic fixed combinations.